Mindfulness at work for dummies - Alidina, Shamash; Adams, Juliet (John Wiley & Sons Ltd., 2014)
Master your mind, manage stress and boost your productivity! Mindfulness at Work For Dummies provides essential guidance for employees at all levels of an organization who are seeking more focus and clarity in their work. It explains how mindfulness can help employers wishing to implement mindful practices into the workplace, and provides leaders and mentors within an organization with the tools they need to become more effective leaders and coaches. The audio download contains guided mindfulness exercises and meditations suited to workplace scenarios, a core feature of m.
Title from title screen. - Includes bibliographical references
Keywords: Self-actualization (Psychology); Awareness; Attention; Meditation; Psychology, Industrial; Employees -- Coaching of; Prise de conscience; Méditation; Psychologie du travail; Employees; Coaching of; Achtsamkeit; Übung; Arbeitswelt